Unraveling the Influence of Arbuscular Mycorrhizal Colonization on Arsenic Tolerance in Medicago: Glomus mosseae is More Effective than G. intraradices, Associated with Lower Expression of Root Epidermal Pi Transporter Genes - Christophersen, Helle M.; Smith, F. A.; Smith, Sally E. (Frontiers in Physiology, 2012)
We used medic (Medicago truncatula) to investigate effects of inoculation with two arbuscular mycorrhizal (AM) fungi and application of arsenate (AsV) and phosphate (Pi) on mechanisms underlying increased tolerance (in terms of growth) of AM plants to AsV. We tested the hypotheses that 1) inoculation with AM fungi results in down-regulation of MtPht1;1 and MtPht1;2 genes (encoding high-affinity Pi- and AsV-uptake systems in the direct root epidermal pathway) and up-regulation of the AM-induced MtPht1;4 (responsible for transfer of Pi from the arbuscular interface to cortical cells), and 2) these changes are involved in decreased As uptake relative to P uptake and hence increased As tolerance. We also measured expression of MtMT4, a Pi starvation-inducible gene, other genes encoding Pi-uptake systems (MtPht 1;5 and MtPht1;6) and arsenate reductase (MtACR) and phytochelatin synthase (MtPCS), to gain insights into broader aspects of P transfers in AM plants and possible detoxification mechanisms. Medic responded slightly to AM colonization in terms of growth in the absence of As, but positively in P uptake. Both growth and P responses in AM plants were positive when As was applied, indicating As tolerance relative to non-mycorrhizal (NM) plants. All AM plants showed high expression of MtPT4 and those inoculated with Glomus mosseae showed higher selectivity against As (shown by P/As molar ratios) and much lower expression of MtPht1;1 (and to some extent MtPht1;2) than G. intraradices-inoculated or NM plants. Results are consistent with increased P/As selectivity in AM plants (particularly those inoculated with G. mosseae) as a consequence of high P uptake but little or no As uptake via the AM pathway. However, the extent to which selectivity is dependent on down-regulation of direct Pi and AsV uptake through epidermal cells is still not clear. Marked up-regulation of a PCS gene and an ACR gene in AM plants may also be involved and require further investigatio